(untitled) (Cardiovascular Journal, 2011)
Background: Accurate diagnosis of heart failure (HF) is essential for its proper management and logical drug therapy to reduce morbidity and mortality. On this perspective researcher are in search of a good biomarker as complementary to the clinical parameters to improve the performance of HF diagnosis. B-type natriuretic peptide (BNP) secreted by cardiac ventricles in HF has emerged as a new promising biomarker in this regard. Objective: To evaluate the performance of plasma BNP as a diagnostic biomarker in HF. Methods: In a cross sectional study 180 clinically suspected HF patients were selected. Their plasma BNP were measured and then subjected to echocardiogram. Patients were categorized as HF and without HF on the basis of echocardiogram and against this information the performance of plasma BNP of study subjects were evaluated as a diagnostic biomarker of HF considering 100 pg/ ml as its cut off point. Results: Sensitivity, specificity, accuracy, PPV, NPV, PLR and NLR of plasma BNP for diagnosis of HF found to be 88 %, 63.8 %, 77.2 %, 75.2 %, 81.0 %, 2.4 and 0.2 respectively. Conclusion: Plasma BNP concentration increases in HF. Based on 100 pg/ml as cut off point, plasma BNP shows good performance in diagnosis of HF Keywords: BNP; Heart failure DOI: http://dx.doi.org/10.3329/cardio.v3i2.9180 Cardiovasc. J. 2011; 3(2): 126-130